2010
DOI: 10.1016/j.jglr.2010.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Recent changes in density, biomass, recruitment, size structure, and nutritional state of Dreissena populations in southern Lake Michigan

Abstract: Recent changes in density, biomass, recruitment, size structure, Recent changes in density, biomass, recruitment, size structure, and nutritional state of and nutritional state of Dreissena Dreissena populations in southern Lake Recent changes in density, biomass, recruitment, size structure, and nutritional state of Dreissena populations in southern Lake Michigan

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
91
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(96 citation statements)
references
References 63 publications
5
91
0
Order By: Relevance
“…They can be performed using laboratory manipulations, mesocosms, and in situ CO 2 perturbation experiments (Fabry et al, 2008). For the Laurentian Great Lakes, one particular genus that should be studied across its life stages is the dreissenid mussel, as these mollusks have significantly shaped the ecosystem since their invasion (Fahnenstiel et al, 2010;Nalepa et al, 2010;Chapra et al, 2012), greatly stress the already-declining native mussels, and make their shells out of aragonite.…”
Section: Box 1 Survey Of Great Lakes Scientistsmentioning
confidence: 99%
“…They can be performed using laboratory manipulations, mesocosms, and in situ CO 2 perturbation experiments (Fabry et al, 2008). For the Laurentian Great Lakes, one particular genus that should be studied across its life stages is the dreissenid mussel, as these mollusks have significantly shaped the ecosystem since their invasion (Fahnenstiel et al, 2010;Nalepa et al, 2010;Chapra et al, 2012), greatly stress the already-declining native mussels, and make their shells out of aragonite.…”
Section: Box 1 Survey Of Great Lakes Scientistsmentioning
confidence: 99%
“…The period [2007][2008] captures conditions associated with the major expansion of quagga mussels into deep water, which started in 2004 Nalepa et al, 2010), and the loss of the spring phytoplankton bloom Vanderploeg et al, 2010); thus, it could represent a critical transition to bottom-up forces strongly affecting zooplankton dynamics. In fact, Kerfoot et al (2010) observed some zooplankton species decreased along cross-lake transects during April in 2007 and 2008 relative to 2006, which they attributed to the loss of the bloom.…”
mentioning
confidence: 99%
“…Similar to the present study, Stoeckmann (2003) observed that D. bugensis at 98C could be induced to spawn by serotonin; whereas, D. polymorpha could not. In a recent study describing changes in dreissenid populations in southern Lake Michigan Nalepa et al (2010) identified differences between adult D. bugensis and D. polymorpha, yet in describing reproductive patterns the resolution of the veliger data did not allow for differentiation between species. For the Nalepa et al (2010) study this was not a great concern because at the time of the most recent sampling no adult D. polymorpha were found suggesting that the veligers were all D. bugensis.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study describing changes in dreissenid populations in southern Lake Michigan Nalepa et al (2010) identified differences between adult D. bugensis and D. polymorpha, yet in describing reproductive patterns the resolution of the veliger data did not allow for differentiation between species. For the Nalepa et al (2010) study this was not a great concern because at the time of the most recent sampling no adult D. polymorpha were found suggesting that the veligers were all D. bugensis. However, for early detection of species a technique is needed to identify species specific veligers.…”
Section: Discussionmentioning
confidence: 99%